Standardization of Bindu Ghrita - Choudhary, Geeta; Meena, Mohar Pal; Sakhitha, K S; Naikare, Trupti (International Research Journal of Ayurveda & Yoga, 2022)
One of the major contributions of Ayurveda is the dosage form called Sneha Kalpana where ghrita and taila are processed in such a way that all the phytochemicals from the plant parts are transferred to the lipid media, mostly the ones which are lipid soluble. The process of making Sneha Kalpana is divided into two steps; the first is Sneha Murchchhana and the second is Sneha Paka. Sneha Murchchhana is performed to remove doshas from the lipid media while Sneha Paka is the preparation of medicated ghrita or taila (Sneha Kalpana). The product obtained after the process of Sneha paka is known as Siddha ghrita or Siddha taila. There are various formulations of Siddha ghrita and Siddha taila given in the Ayurveda text. Bindu Ghrita is one of the formulations of ghrita, mentioned in Ayurveda texts like Chakradatta, Sharangadhara Samhita, Bhaishajya Ratnavali, Gadanigraha and Yoga Ratnakara. The word Bindu suggests its therapeutic use indicating the number of Bindus applied on the Nabhi ( umbilicus ) which is equal to the number of Virechana Vega ( purgations ). Internal use of Bindu Ghrita is also suggested in some texts. Bindu Ghrita is used to treat Udara rogas mainly in Jalodara (Ascites). Its other indications are as Kushtha, Aadhmana, Mandaagni, Gulma etc. There have been very few works done on this formulation, and no work on the standardization of Bindu Ghrita has been undertaken till date. This study focuses on the pharmaceutical as well as analytical standardization of Bindu Ghrita as per the reference of Sharangadhara Samhita and is one of the first studies reported on its standardization.